Identifying factors associated with sedentary time after stroke. Secondary analysis of pooled data from nine primary studies. Issue 5 (4th July 2019) - Hendrickx, Wendy; Riveros, Carlos; Askim, Torunn; Bussmann, Johannes B.J.; Callisaya, Michele L.; Chastin, Sebastien F.M.; Dean, Catherine M.; Ezeugwu, Victor E.; Jones, Taryn M.; Kuys, Suzanne S.; Mahendran, Niruthikha; Manns, Trish J.; et al.
ABSTRACT: Background : High levels of sedentary time increases the risk of cardiovascular disease, including recurrent stroke. Objective : This study aimed to identify factors associated with high sedentary time in community-dwelling people with stroke. Methods : For this data pooling study, authors of published and ongoing trials that collected sedentary time data, using the activPAL monitor, in community-dwelling people with stroke were invited to contribute their raw data. The data was reprocessed, algorithms were created to identify sleep-wake time and determine the percentage of waking hours spent sedentary. We explored demographic and stroke-related factors associated with total sedentary time and time in uninterrupted sedentary bouts using unique, both univariable and multivariable, regression analyses. Results : The 274 included participants were from Australia, Canada, and the United Kingdom, and spent, on average, 69% (SD 12.4) of their waking hours sedentary. Of the demographic and stroke-related factors, slower walking speeds were significantly and independently associated with a higher percentage of waking hours spent sedentary (p = 0.001) and uninterrupted sedentary bouts of >30 and >60 min (p = 0.001 and p = 0.004, respectively). Regression models explained 11–19% of the variance in total sedentary time and time in prolonged sedentary bouts. Conclusion : We found that variability in sedentary time of people with stroke was largely unaccounted for by demographic and stroke-related variables. Behavioral and environmental factors are likely to play an important role in sedentary behavior after stroke. Further work is required to develop and test effective interventions to address sedentary behavior after stroke.